Venous access made easy - Forsyth, James Michael; Shalan, Ahmed; Thompson, Andrew (Andrew Roger) (Boca Raton : CRC Press, 2018)
This bookprovides simple and practical instructions on how to perform safe and easy venous cannulation, and how to insert midlines and PICC lines using ultrasound. It aidsunderstanding ofthe relevant anatomy, shows how to use the ultrasound machine, and how to insert such lines using ultrasound guidance. Readers will feel confident and well prepared to deal with patientsrequiring difficult venous access, giving them simple solutions that can be learned very quickly. These skills will also be globally beneficial for patients and healthcare institutions alike. Follows the trends of the NHS and riding the wave of the midline/PICC line revolution Compact and affordable highly relevant to daily practice Useful for specialists and generalists alike, truly multi-disciplinary
Venous access glossary -- Venous anatomy -- Basic ultrasound use -- Venous access assessment -- Choosing the right venous access approach -- Peripheral venous cannulation -- Ultrasound guided peripheral cannulation -- Midline insertion -- PICC line insertion -- Care & maintenance of venous lines -- Complications -- Single best answer assessment.
OCLC-licensed vendor bibliographic record.
Keywords: Catheterization; Ultrasonic imaging; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; MEDICAL / General; MEDICAL / Radiology & Nuclear Medicine; MEDICAL / Surgery / General